Habilidades sociales en niños de 5 años, del nivel inicial Red N° 10 del Callao - Puppo La Roche, Nancy Genoveva (2012)
This descriptive study was to determine the levels of social skills that are the children of five years of the educational institutions of the network N° 10 of the Callao District. The participants were 120 children from low socioeconomic level, which were randomly selected. The instrument applied was The Scale of Assessment of Social Skills in Childhood, (Paula, 2000), by the proposed teaching staff. Results showed that they exist in children levels low of basic social skills, of social interaction, initiation of social interaction skills and conversational skills, ability to cooperate and share, selfaffirmation and skills in the skills related to the emotions and feelings the level is under the level equivalent medium.